Vozes trans : um estudo etnográfico sobre a construção da identidade de gênero das pessoas trans - Robalo, Diego (2014)
What is this strange body that inhabits a diverse heteronormative, patriarchal and sexist society? Every time we turn on the television we see numerous social identities. However, we remain inert to the social issue of trans people and before the whole tangle of issues around their images, their profiles and their names. Identity and gender are not only social categories, social elements or individual stocks. Are more than categories of society. When we speak of trans reality these are the tools that reshape, back and reconstruct what is right or wrong for society. What rules bind us and which distance us transgender people? There is a woman in a male body as they construct their identities? It emerges from the break that different from each other, the exotic, that breaks the normalcy that crack social life, provoking thought and debate. What moves this group socially? There is an empowerment of citizenship of these people? The trans world, with his difficulties, realities and paths, the embezzlement of trans people in the social space, the process of struggles and battles of a different seeking a new, going against the whole society. The trans dialogues emerge from spaces of empowerment, breaking and daily debates that different. The trans voices present in this dissertation emerge from space that is still in training, people in their social paths, somehow, are demonstrative of political empowerment, the reality that not all hits. I invite everyone to dialogue about trans people, their life stories, their speech and their claim, watching the other not only as an invisible in our society, but as someone who participates is present and promotes reflection of what we consider right or wrong, normal or abnormal, good or bad. Let's demystify through the speech of individuals, using elements that emerge from all social fields, such as non-governmental organizations, social networks, newspapers, political spaces, social movements and everyday life of our informants.